Big Five traits predict stress and loneliness during the COVID-19 pandemic: Evidence for the role of neuroticism. (May 2022) - Ikizer, Gözde; Kowal, Marta; Aldemir, İlknur Dilekler; Jeftić, Alma; Memisoglu-Sanli, Aybegum; Najmussaqib, Arooj; Lacko, David; Eichel, Kristina; Turk, Fidan; Chrona, Stavroula; Ahmed, Oli; Rasmussen, Jesper; et al.
Abstract: The rapid outbreak of the coronavirus disease (COVID-19) has affected citizens' daily lives in an unprecedented way. To curb the spread of the pandemic, governments have taken numerous measures such as social distancing and quarantine, which may be associated with psychological consequences, namely stress and loneliness globally. To understand differential associations of personality traits with psychological consequences of COVID-19, we utilize data from a sample of 99, 217 individuals from 41 countries collected as part of the COVIDiSTRESS Global Survey. Data were analyzed using multigroup confirmatory factor analysis and multilevel regression models. Findings showed that while some of the associations were rather weak, Big Five personality traits were significantly associated with perceived stress and loneliness during the pandemic. Our study illustrates that neuroticism especially can be a vulnerability factor for stress and loneliness in times of crisis and can contribute to detection of at-risk individuals and optimization of psychological treatments during or after the COVID-19 pandemic. Highlights: A dataset with 99, 217 responses from 41 countries was analyzed. Big Five traits, especially neuroticism, were associated with pandemic-related stress and loneliness. Results can help in mapping profiles of who are at risk for adverse outcomes.